Keseimbangan Emosi dan Jiwa: Studi Korelasional tentang Regulasi Emosi dan Kesejahteraan Psikologis pada Siswa - Rakasiwy, Mochamad Randy Pradika; Satwika, Yohana Wuri (Universitas Negeri Malang, 2025)
The decline in psychological well-being among students is a global phenomenon, largely influenced by the unstable nature of adolescent life and the complex challenges they face in academic, social, and other aspects. This study examines the relationship between emotion regulation and psychological well-being among high school students in Surabaya. The research employed a quantitative correlational method and involved a sample of 427 students. Emotion regulation and psychological well-being were measured using validated scales. The results indicated that the majority of students reported a low level of psychological well-being (56,9%), while the level of emotion regulation was predominantly in the high category (44,3%). Data analysis revealed a moderately strong correlation between the two variables, with a correlation coefficient of 0.465. The p-value for the relationship between emotion regulation and psychological well-being was 0.000. At a significance level of 0.05, the p-value of 0.000 indicates a statistically significant result; thus, the null hypothesis is rejected. Therefore, the two variables are significantly associated. This study highlights a positive correlation between students’ emotion regulation and their psychological well-being. AbstrakPenurunan kesejahteraan psikologis di kalangan pelajar merupakan fenomena yang terjadi secara global yang disebabkan oleh fase kehidupan pelajar yang cenderung tidak stabil dan dihadapkan permasalahan kompleks pada aspek akademik, sosial, maupun isu lainnya. Studi ini mengkaji hubungan regulasi emosi dengan kesejahteraan psikologis pada siswa sekolah menengah atas di Kota Surabaya. Metode yang digunakan dalam penelitian ini adalah kuantitatif korelasional dan melibatkan 427 siswa sebagai sampel. Regulasi emosi dan kesejahteraan psikologis diukur menggunakan skala yang telah tervalidasi. Hasil menunjukkan mayoritas siswa menunjukkan skor kesejahteraan psikologis pada taraf rendah yakni sebesar 56,9%, sedangkan skor regulasi emosi pada taraf tinggi yakni 44,3%. Hasil analisis data menunjukkan adanya korelasi yang cukup kuat antara kedua variabel, dengan koefisien korelasi sebesar 0,465. Nilai p-value antara regulasi emosi dan kesejahteraan psikologis adalah 0,000. Pada taraf signifikansi 0,05, nilai p sebesar 0,000 menunjukkan bahwa hasil uji signifikan, sehingga hipotesis nol ditolak. Dengan demikian, kedua variabel memiliki hubungan yang signifikan secara statistik. Penelitian ini mengungkapkan bahwa regulasi emosi siswa berkorelasi positif dengan kesejahteraan psikologis.